2003
DOI: 10.1128/jb.185.5.1705-1711.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cytosolic NiFe-Hydrogenase from the Hyperthermophilic Archaeon Thermococcus kodakaraensis KOD1

Abstract: We have identified an NiFe-hydrogenase exclusively localized in the cytoplasm of the hyperthermophilic archaeon Thermococcus kodakaraensis KOD1 (T. kodakaraensis hydrogenase). A gene cluster encoding T. kodakaraensis hydrogenase was composed of four open reading frames (hyhBGSL Tk ), where the hyhS Tk and hyhL Tk gene products corresponded to the small and the large subunits of NiFe-hydrogenase, respectively. A putative open reading frame for hydrogenase-specific maturation endopeptidase (hybD Tk ) was found d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…In contrast, the homologous proteins in Methanococcus jannaschii and Methanobacterium thermautotrophicum also have Arg rather than His residues at this position and yet contain carboxy-terminal extensions that likely undergo proteolytic processing (241). Finally, although the maturation process experienced by archaeal hydrogenases has been less well characterized than the parallel process in Bacteria, archaeal homologues of bacterial enzymes involved in this posttranslational maturation process have been described (199,428).…”
Section: Carboxy-terminal Maturation Of Archaeal [Nife] Hydrogenasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the homologous proteins in Methanococcus jannaschii and Methanobacterium thermautotrophicum also have Arg rather than His residues at this position and yet contain carboxy-terminal extensions that likely undergo proteolytic processing (241). Finally, although the maturation process experienced by archaeal hydrogenases has been less well characterized than the parallel process in Bacteria, archaeal homologues of bacterial enzymes involved in this posttranslational maturation process have been described (199,428).…”
Section: Carboxy-terminal Maturation Of Archaeal [Nife] Hydrogenasesmentioning
confidence: 99%
“…In Escherichia coli and other Bacteria, the hydrogenase cleavage motif is followed by a stretch of 15 or more amino acid residues (53). By contrast, in the proteolytic processing of the Thermococcus kodakaraensis hydrogenase ␣ subunit, only four amino acid residues were released from the carboxy terminus following the conserved cleavage motif (199).…”
Section: Carboxy-terminal Maturation Of Archaeal [Nife] Hydrogenasesmentioning
confidence: 99%
“…Because a small amount of H 2 was still generated in the ⌬mbhJKL strain grown in MA-YT-S 0 , this might be due to Hyh functioning in the reverse direction. It has previously been demonstrated that Hyh can generate H 2 with NADPH as an electron donor (15).…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, Tk-GDH acts to suppress the oxidation of amino acids. The electrons, or NADPH, needed to reduce 2-oxoacids may be supplied by the NADP-dependent cytosolic hydrogenase (Hyh), which can utilize the molecular hydrogen generated by T. kodakarensis in ASW-YTPyr medium (54,55). This mechanism does provide an advantage, as cells would be able to prevent excess consumption of the amino acid pool and rely more on the oxidation of the excess pyruvate for reducing equivalents and ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%